Molecular investigation of coleopteran specific alpha-amylase inhibitors from amaranthaceae members - Rane, Ashwini S.; Venkatesh, Varun; Joshi, Rakesh S.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2020)
alpha-Amylase inhibitors (alpha-AIs) target alpha-amylases and interfere with the carbohydrate digestion of insects. Among different classes of alpha-AIs, a knottin-type inhibitor from Amaranthus hypochondriacus (AhAI) was found to be specific against coleopteran storage pests. In this report, we have characterized three previously unidentified knottin-type alpha-AIs from various Amaranthaceae plants namely, Amaranthus hypochondriacus (AhAI2), Alternanthera sessilis (AsAI) and Chenopodium quinoa (CqAI). They contain a signal peptide, pro-peptide, and mature peptide. The mature peptides of the new alpha-AIs shared 68 to 78% identity with AhAI and have highly variable pro-peptide regions. Along with the cystine-knot fold, they showed conservation of reactive site residues. All recombinant alpha-AIs were successfully expressed in their active form and native state using an oxidative cytoplasmic environment. Inhibition studies against various amylases revealed that these inhibitors showed selective inhibition of coleopteran recombinant insect alpha-amylases viz., Tribolium castaneum, and Callosobruchus chinensis. Tribolium castaneum alpha-amylase inhibition potency was highest for AhAI2 (Ki similar to 15 mu M) followed by AsAI (Ki similar to 43 mu M) and CqAI (Ki similar to 61 mu M). Interaction analysis of these inhibitors illustrated that the reactive site of inhibitors make several non-covalent interactions with the substrate-binding pocket of coleopteran alpha-amylases. The selectivity of these inhibitors against coleopteran a-amylases highlights their potential in storage grain pest control. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: alpha-amylase; alpha-amylase inhibitor; Amaranthaceae; Coleoptera; Knottin-type